Digit ratio (2D:4D) as an indicator of body size, testosterone concentration and number of children in human males. (November 2014) - Klimek, Magdalena; Galbarczyk, Andrzej; Nenko, Ilona; Alvarado, Louis Calistro; Jasienska, Grazyna
Abstract Objectives: The 2nd to 4th digit ratio (2D:4D) is thought to reflect exposure to androgens during foetal development. This study examined the relationship between low (more masculine) and high (more feminine) 2D:4D and body size at different stages of the life course, adult testosterone levels and number of children among males. Methods: Five hundred and fifty-eight men from rural Poland at the Mogielica Human Ecology Study Site participated in this study. Life history data and anthropometric measurements were collected. Salivary morning and evening testosterone levels among 110 men from the same population were measured. Results: Low 2D:4D was related to higher birth weight (p = 0.04), higher birth length (p = 0.01), higher body mass during childhood and adolescence (p = 0.01), higher BMI (borderline significance, p = 0.06), higher number of children among fathers (p = 0.04) and higher testosterone levels during adulthood (p = 0.04). Conclusions: This study shows, for the first time in a single population, that digit ratio is related to sub-adult body size at different stages of the life course, adult testosterone levels and number of children. The observed results suggest that digit ratio might be a valuable predictor of male body size and reproductive characteristics.